Tingkat Self Awareness Mahasiswa Bimbingan dan Konseling Angkatan 2017 Universitas Negeri Malang Sebagai Kesiapan Menjadi Konselor Sekolah - Aulia Fiki Aprina; Irene Maya Simon; Djoko Budi Santoso; Aulia Fiki Aprina; Irene Maya Simon (Universitas Negeri Malang, 2021)
Abstract: Self awareness is an individual's ability to recognize themselves and potential. Self awareness is important for guidance and counseling students to identify their own weaknesses and strengths, attitudes toward others, and manage emotions as readiness becomes school counselors. This research aims to describe the level of self-awareness of guidance and counseling students of 2017 class State University of Malang for readiness to become school counselors. The research used a quantitative approach with a survey as a data collection method. Survey research is used to gather information about self-awareness through statements. 30 percent of the population is used for trials and 70 percent is used for samples. The sampling technique is probability sampling. Data collection using a questionnaire using percentage analysis techniques. The results showed that the overall level of self-awareness was in high (81 percent), medium (19 percent), low (0 percent) categories. The level of self-awareness on the attention aspect is in high (99 percent), medium (1 percent), low (0 percent) categories. The level of self-awareness on the wakefulness aspect is in the high (66 percent), medium (34 percent), low (0 percent) category. The level of self-awareness in the architecture aspect is in high (73 percent), medium (27 percent), low (0 percent) categories. The level of self-awareness on the aspect of recall of knowledge is in high (84 percent), medium (16 percent), low (0 percent) categories. The level of self-awareness on the emotive aspect is in the high (93 percent), medium (7 percent), low (0 percent) category. Based on these data, it concluded that the level of self-awareness of guidance and counseling students of 2017 class State University of Malang tends to be high. Abstrak: Self awareness adalah kemampuan individu untuk mengenali diri dan potensi. Self awarenes penting bagi mahasiswa bimbingan dan konseling untuk mengetahui kelemahan dan kelebihan diri sendiri, sikap diri terhadap orang lain, dan kelola emosi sebagai kesiapan menjadi konselor sekolah. Penelitian bertujuan untuk mendeskripsikan tingkat self awareness mahasiswa bimbingan dan konseling angkatan 2017 Universitas Negeri Malang sebagai kesiapan menjadi konselor sekolah. Rancangan penelitian menggunakan pendekatan kuantitatif dengan survei sebagai metode pengumpulan data. Penelitian survei digunakan untuk mengumpulkan informasi terkait self awareness mahasiswa melalui daftar pernyataan. 30% dari populasi digunakan untuk uji coba dan 70 persen digunakan untuk sampel. Teknik pengambilan sampel ialah probability sampling. Pengumpulan data menggunakan angket dengan pengolahan data menggunakan teknik analisis persentase. Hasil penelitian menunjukkan tingkat self awareness secara keseluruhan dalam kategori tinggi (81 persen), sedang (19 persen), rendah (0 persen). Tingkat self awareness pada aspek attention dalam kategori tinggi (99 persen), sedang (1 persen), rendah (0 persen). Tingkat self awareness pada aspek wakefulness dalam kategori tinggi (66 persen), sedang (34 persen), rendah (0 persen). Tingkat self awareness pada aspek architecture dalam kategori tinggi (73 persen), sedang (27 persen), rendah (0 persen). Tingkat self awareness pada aspek recall of knowledge dalam kategori tinggi (84 persen), sedang (16 persen), rendah (0 persen). Tingkat self awareness pada aspek emotive dalam kategori tinggi (93 persen), sedang (7 persen), rendah (0 persen). Berdasarkan data tersebut, disimpulkan bahwa tingkat self awareness mahasiswa bimbingan dan konseling angkatan 2017 Universitas Negeri Malang cenderung tinggi.